Perceptions of CAL, CS and CSSP students of University of the Philippines on the status of the library and information profession - Baselonia, Alma S.; Faderon, Rosalie B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2002)
The problem of status has been of concern to the library and information profession for years. Compared to other professions, the status of the library and information profession is low.
This study focused on the perceptions of CAL.CS and CSSP students of UP Diliman on the status of the library and information profession. It was conducted to determine the probable causes that contribute to the perceived low status. Moreover, it aimed to determine if there has been any change in the position of the library and information profession in the occupational status ladder.
Out of 4,331 undergraduate students of CAL, CS and CSSP of UP Diliman, some 366 were taken as samples. Students were then categorized according to age, gender and college for comparative purposes. A questionnaire patterned after the one used by Hans Prins and Wilco de Gier (1995) was used in data gathering. Gathered data were tabulated and analyzed using the following statistical tools: computations of mean; frequency counts; and percentages. Tables and graphs were used to present the data.
Findings of the study revealed that CAL, CS and CSSP students did not perceive the status of the library and information to be low. However, these students believe that library and information professionals should be concerned with their status. Among the perceived causes of the low status were: little knowledge of librarian's work; poor quality of service; poor/low salary; the library's marginal role in the development of the economy; no distinction between librarians and other employees; nonawareness of the librarian's management responsibility, insufficient funding; nonawareness of librarian's social responsibility; and, no professional education needed. There were hardy any differences in perceptions among students with different ages, gender and colleges. Moreover, findings of the study showed that the position of the library and information profession in the occupational status fell one notch, from 5th to 6th.To improve the present status of the profession, recommendations to the library schools, library and information centers, library organizations and associations and library and information professionals were suggested.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines -- Students; College students -- Philippines -- Quezon City; Library science